Thermoplasmonic and Photothermal Metamaterials for Solar Energy Applications - Shin, Dongheok; Kang, Gumin; Gupta, Prince; Behera, Saraswati; Lee, Hyungsuk; Urbas, Augustine M.; Park, Wounjhang; Kim, Kyoungsik (WILEY-V C H VERLAG GMBH, 2018)
Sunlight is one of the Earth's clean and sustainable natural energy resources, and extensive studies are conducted on the conversion of solar energy into electricity using photovoltaic (PV) devices. However, single-junction PV devices cannot break the theoretical efficiency limit known as the Shockley-Queisser limit that is caused by the sub-bandgap transmission and heat dissipation losses in semiconductors. Solar thermal conversion approaches may provide an alternative way to exceed this limit and enable more efficient use of solar light than that in PV devices. Recently, spectrally or thermally engineered metamaterials have attracted considerable attention for solar energy applications because of their excellent physical properties. The recent research progress in the development of these photothermal and thermoplasmonic metamaterials, along with their promising applications in solar thermophotovoltaics, radiative cooling, and solar desalination, is discussed.
Keywords: CONVERSION EMISSION ENHANCEMENT; UP-CONVERSION; STEAM-GENERATION; HIGH-EFFICIENCY; PLASMON ENHANCEMENT; PHOTONIC STRUCTURES; OPTICAL-ABSORPTION; SILICON NANOWIRE; VAPOR GENERATION; LIGHT